VOLUNTARY DISCLOSURE PROGRAM IN PERSPECTIVE OF THE LAW ON THE HARMONIZATION OF TAX REGULATIONS - Herianto Herianto (Journal Philosophy of Law, 2023)
The promulgation of the Law on the Harmonization of Tax Regulations through Law Number 7 of 2021 has brought a new paradigm in regulations related to taxation in Indonesia. One of the new provisions in a quo provision is related to the material governing the Voluntary Disclosure Program. This article will try to explain the history of tax amnesty regulations in Indonesia and the concept of the Voluntary Disclosure Program as a new tax policy in Indonesia. This article is a conceptual article that uses a conceptual and analytical approach as support in analysis. The data used is based on secondary data. The results showed that the Policy regarding tax amnesty in Indonesia has been in effect since the New Order era until 2021. After the enactment of Law Number 7 of 2021, the tax amnesty program changed to the Voluntary Disclosure Program. This Voluntary Disclosure Program allows all taxpayers to disclose their assets that have not or are not disclosed. One of the objectives of this program is to increase the voluntary compliance of taxpayers organized based on the principles of simplicity, legal certainty, and practicality.